Biomimetic Enamel Regeneration Mediated by Leucine-Rich Amelogenin Peptide. (May 2017) - Kwak, S.Y.; Litman, A.; Margolis, H.C.; Yamakoshi, Y.; Simmer, J.P.
We report here a novel biomimetic approach to the regeneration of human enamel. The approach combines the use of inorganic pyrophosphate (PPi ) to control the onset and rate of enamel regeneration and the use of leucine-rich amelogenin peptide (LRAP), a nonphosphorylated 56–amino acid alternative splice product of amelogenin, to regulate the shape and orientation of growing enamel crystals. This study builds on our previous findings that show LRAP can effectively guide the formation of ordered arrays of needle-like hydroxyapatite (HA) crystals in vitro and on the known role mineralization inhibitors, like PPi, play in the regulation of mineralized tissue formation. Acid-etched enamel surfaces of extracted human molars, cut perpendicular or parallel to the direction of the enamel rods, were exposed to a PPi -stabilized supersaturated calcium phosphate (CaP) solution containing 0 to 0.06 mg/mL LRAP for 20 h. In the absence of LRAP, PPi inhibition was reversed by the presence of etched enamel surfaces and led to the formation of large, randomly distributed plate-like HA crystals that were weakly attached, regardless of rod orientation. In the presence of 0.04 mg/mL LRAP, however, densely packed mineral layers, comprising bundles of small needle-like HA crystals, formed on etched surfaces that were cut perpendicular to the enamel rods. These crystals were strongly attached, and their arrangement reflected to a significant degree the underlying enamel prism pattern. In contrast, under the same conditions with LRAP, little to no crystal formation was found on enamel surfaces that were cut parallel to the direction of the enamel rods. These results suggest that LRAP preferentially interacts with ab surfaces of mature enamel crystals, inhibiting their directional growth, thus selectively promoting linear growth along the c -axis of enamel crystals. The present findings demonstrate a potential for the development of a new approach to regenerate enamel structure and properties.